Foreign Direct Investments: A Literature Review - Letsou, Eleni; Pantelidis, Pantelis (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this paper is to offer the literature evaluation of the concept of foreign direct investments and the crucial context related to this to have a look at. It's a reality that markets’ globalization and internationalization of monetary individuals of the circle of relatives that have existed inside the course of the state-of-the-art years have caused a rapid growth in exchange flows, cash, and capital flows. In such situations, the multinational firms play the most crucial characteristic within the development of overseas direct investments. First of all, there is a conceptual method to the kinds of international sports as well as the clean definitions regarding foreign direct investments. Therefore, it follows an outline of the reasons for the implementation of overseas direct investments and their paperwork. The 3 most important types of overseas direct investments, the factors that lead a business enterprise to their popularity, and the incentives to draw them are indexed in this paper. The literature examined for this take a look at concludes with the essential empirical studies finished on outward overseas direct investments.